ECISION SUPPORT SYSTEM IN PROVIDING PEOPLE'S BUSINESS CREDIT (KUR) USING THE WEIGHTED PRODUCT (WP) METHOD AND WEB-BASED TOPSIS - Mario, Deka; Agustina, Nabela; Parida, Meri; Afandi, Asep (Institut Bakti Nusantara, 2023)
People's Business Credit (KUR) is a credit that gets subsidized facilities from the government, one of which is KUR BRI. The government itself recently extended the BRI KUR ceiling without collateral or collateral for loans of up to IDR 100 million with interest subsidies of up to 3 percent. For the credit given to be smooth, the bank must be selective in giving credit to creditors, whereas before credit is given to the debtor, the bank must analyze the provision of credit to determine the creditor's ability to repay the loan by the terms contained in the loan agreement [2]. A decision support system (DSS) is a system that helps decision-makers in unstructured decision conditions and non-semi-structured situations. Metode Weighted Product (WP) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). part of the Multi-Attribute decision-making (MADM) is used to rank all alternatives from predetermined criteria and sub-criteria. The implementation of the two methods for the ten alternatives (BRI Kotabumi Branch) turned out to give very good results using these two methods. The calculation results of these two methods are the same, so it can be concluded that the most feasible results from the WP and TOPSIS methods are Alternative 5 Initials A with WP values 0.134 and TOPSIS 0.774